Complement Markers in Blood and Urine: No Diagnostic Value in Late Silent Antibody-Mediated Rejection. Issue 7 (July 2019) - Mező, Blanka; Heilos, Andreas; Böhmig, Georg A.; Eskandary, Farsad; Wahrmann, Markus; Bond, Gregor; Kozakowski, Nicolas; Halloran, Philip F.; Rusai, Krisztina; Prohászka, Zoltán
Abstract : Background: Antibody-mediated rejection (AMR) is a major cause of kidney allograft failure. Its molecular mechanisms are multifaceted and may include a role of complement activation via the classical pathway. Here, we investigated whether noninvasive complement monitoring adds predictive power to the diagnosis of AMR in the setting of donor-specific antibody (DSA) positivity. Methods: In this cross-sectional study, 741 kidney transplant recipients with stable graft function ≥180 days posttransplantation were screened for the presence of human leukocyte antigen (HLA) alloantibodies. Eighty-three of 111 DSA-positive recipients underwent protocol biopsies and were tested for blood and urinary levels of complement proteins (C1q, C4, C3) and activation products (C4d, C3a, C5a, C5b-9). Results: Forty-seven recipients were diagnosed with AMR, and 21 were C4d-positive. While biopsy-confirmed AMR (and C4d) associated with DSA-binding strength (IgG mean fluorescence intensity of the immunodominant DSA versus AMR; area under the receiver operating characteristic curve: 0.76), tested complement markers did not have any predictive value for rejection (area under the receiver operating characteristic curve: 0.49–0.56). There were, however, tight correlations between complement activation products in urine and protein/creatinine ratio ( ρ = 0.44–0.64; P < 0.001). Analysis of death-censored graft survival over a median of 60 months revealed no independent associations with levels of complement markers in blood or urine. Conclusions: Complement patterns in blood and urine failed to identify AMR in late biopsies and may have no relevant diagnostic value in this particular context.